Perception of teaching process learning in indigenuos school education: multiple views at the Morro Branco village in the municipality of Grajau/Maranhão (Research, Society and Development, 2020)
This research discusses the problematic of the teaching-learning process in the Early Years of Elementary School at Aldeia Morro Branco, an indigenous school located in the city of Grajaú-MA. Its central objective is to understand how the process of teaching and learning occurs in the villages from the teachers' perception. Indigenous Education is a fundamental political-educational action for the maintenance of Brazilian indigenous culture, constituting a process of transmission of ancestral knowledge built by indigenous populations. Indigenous School Education refers to formal educational actions, through an educational process based on interculturality and bilingualism. From the methodological point of view, the research was based as a qualitative research. It was found that much remains to be done to make the process of an emancipatory education in the village of Morro Branco, which portrays the reality of many villages in the country, reaching the fundamental principles for Indigenous Education able to meet recovery needs and preservation of indigenous peoples and culture.